Context matters in MLL-AF9–driven leukemias - Park, Christopher Y. (Blood, 2016)
In this issue of Blood, Man et al demonstrate that the transforming activity of the leukemic fusion oncogene MLL-AF9 is regulated by inhibitor of DNA binding 1 (Id1), a dominant-negative regulator of E protein transcription factors.(1)